Dos sujeitos e lugares da punição: da passagem do/a jovem perigoso/a para o/a jovem em perigo: um estudo das dimensões do dispositivo da gestão dos riscos e de controle social da juventude - Teixeira, Joana D Arc [UNESP] (2015)
This thesis investigates the dimensions of social control devices of youth in order to describe the effects of a punitive society in the production processes of the young and young criminalized people and the set up places for punishment, considering the institutions for young women as privileged places for this description. The specific goal is to identify, examine and map the transition of a tutelary-correctional-repressive system into a state policy one, where there are different punitive forms, which delimit the composition and distribution of the subjects of punishment from the risk management justification. Three distinct periods in the constitution in the history of social and educational care of these last twenty years have been defined as an analytical field: (1) re-democratization context of Brazil, advocacy and recognition of young people as subjects of rights - the early 1990; (2) promulgation and implementation of the Statute of Children and Adolescents; (3) process of reconfiguring the socio-educational system of admission: municipalization and decentralization of care, the late 1999 - 2010, reaffirming the context of the CASA Foundation (Socio Foundation Care Centre for Adolescents) service policies and implementation of SINASE (National System of Socio-Education) process. For the constitution and analysis of this thesis, the following points were also prioritized: field survey, semi-structured interviews with young people and other actors that make up the structure of the socio-educational system. In theoretical and methodological terms, the theoretical and analytical construction on government policies that extends to young men and women in social-educational system is sought in the international and national production, especially the study of punitive trends from authors who defend thesis of an ongoing process of punitive hardening, the emergence of a culture of control and a new design in addition to the disciplinary...